Health, human capital and economic growth in Brazil - Antonio Campino; Carlos Augusto Monteiro; W.L. Conde; F.M.S. Machado (European Regional Science Association (ERSA), 2004)
The main objective of the research is to analyze the relationship between population health status, and processes of economic growth and social development in Brazil by exploring the use of the population's nutritional and health variables to assess the quality of human capital and the mechanisms through which these variables may impact the country's economic performance in terms of human capital formation, long-term economic growth, and social development. This research includes considerations on recent advances in the economic growth theory that contains the relationship between health, human capital, and long-term economic growth, as well as empirical evidence obtained from the analysis of an important Brazilian database, the Living Standards Measurement Survey, (Pesquisa de Padrao de Vida - PPV), a household survey conducted between 1996 and 1997 in both the Southeast and Northeast Regions of Brazil. The first part of the study focuses on information from individuals belonging to the group of economically active population (people between 19 and 59 years-old, both genders) to analyze the connection of individuals' health variables, such as height and health status, with socioeconomic variables, like income and educational attainment, controlling by area of residence (rural vs urban) and region (Northeast vs Southeast) The second part of the study focuses on information from individuals belonging to the group of economically active population (19 to 59 years-old both genders) with at least one child to support (2 to 21 years-old, both genders) in order to evaluate the intergenerational transmission of human capital, that is, analyzing the relations among parents data on health and nutritional status, income and educational attainment and the investment he/she is providing to the formation of human capital of his/her own child, controlling by area of residence (rural vs urban) and region (Northeast vs Southeast). Results lead to the conclusion that improvements generated through human capital investments made in one individual by the family do not finish at the individual himself, but are propagated to the next generations, independently from mechanisms of income. That is, relevant investments in human capital development, as educational attainment, nutrition, and health, create better opportunities to the individual in terms of employment and income. However, beyond these primary effects, there are secondary effects, mainly based on the transmission of human capital formation through generations, that result in population lifestyle changes, economic growth and development.
Keywords: 330